Smart farming for marginal farmers: implementing IoT-based irrigation systems through community workshops - Matsaini (CV Narasi Khatulistiwa Indonesia, 2026)
Background: This community service addresses persistent water inefficiency and technological exclusion among marginal farmers in rain-fed agricultural areas of East Java. Objective: The program aimed to enhance farmers’ capacity to adopt and operate simple IoT-based irrigation systems through participatory workshops and field mentoring. Method: A participatory approach was implemented, combining planning, hands-on training, demonstration plots, and continuous mentoring with monitoring and evaluation. Results: The program led to reduced irrigation frequency and water use, improved crop uniformity, and increased farmer autonomy, alongside gains in technological understanding and shifts toward data-driven irrigation decisions, supported by collective learning and institutional engagement. Implication: These findings suggest that affordable, community-based smart farming interventions can improve resource efficiency and strengthen technological inclusion among marginal farmers. Novelty: The program introduces an adaptive IoT-based irrigation model that integrates low-cost technology, participatory learning, and shared governance as a scalable approach for sustainable agriculture in resource-constrained settings.